Delmar's critical care/surgical care nursing skills CD-ROM - Altman, Gaylene Bouska; Buchsel, Patricia; Coxon, Valerie; Delmar Thomson Learning (Albany ; Delmar Thomson Learning, 2000)
'Over 50 critical care/surgical care nursing skills are contained on this CD-ROM including blood administration, advanced respiratory, tubes, ventilation, central lines, pre/postoperative care, dressings and wound care.' -- from box
System requirements: 100 MHz Pentium w/24 MB of RAM; Windows 95 or newer; CD-ROM drive (8x or faster); sound card and speakers; SVGA 24-bit color display; 8 MB of free disk space
Keywords: Nursing Care; Critical care